PRRI Suppression Operation in Sungai Pagar (1958-1961): Operasi Penumpasan PRRI di Sungai Pagar (1958-1961) - Cindy Lorenza; Bunari; Asyrul Fikri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The establishment of PRRI was a reaction to the leadership of President Soekarno and to create a more decentralized government in Indonesia. The first joint operation known as Operation Tegas led by Lieutenant Colonel (Inf) Kaharuddin Nasution in Pekanbaru.The research problem was the destruction process of PRRI in Sungai Pagar, Kampar Kiri Hilir in 1958-1961. This research aims to (1) know the background of the emergence of PRRI in Riau (2) to know the PRRI movement that occurred in Sungai Pagar 1958-1961 (3) to know the actions in an effort to suppress PRRI in Sungai Pagar by the Republican Army. This research is a library research study. The method used in this research is qualitative historical methods covering four stages including: heuristic, critism, interpretation, and historiography. As for the location of the research that is in Sungai Pagar Village, Kampar Kiri Hilir District, Riau Province. The result showed that the destruction of PRRI in Sungai Pagar was based on the involvement of US CIA who provided weapons and drop it at Pekanbaru and Sungai Pagar village which is approximately 30km from Pekanbaru became one of the areas used by PRRI troops in resistance to the Republican army.